EARLY OUTCOME OF CORONARY ARTERY BYPASS GRAFTING IN PATIENTS WITH UNSTABLE ANGINA - Paras, Iftikhar; Bakhsh, Allah; Hussain, Ghulam; Munir, Khalid; Khan, Yasir; Moeen, Muhammad (Journal of Ayub Medical College Abbottabad, 2014)
Background: Unstable angina is a common causeof admission to hospitals. There is conflicting evidence on the need and success of urgent coronary revascularization in such cases. This study was conducted to evaluate the early post-operative morbidity and mortality of Coronary Artery Bypass Grafting (CABG) in patients with unstable angina. Methods: This cross sectional descriptive study was conducted at Choudry Pervaiz Elahi Institute of Cardiology, Multan. The data of the all the patients who had undergone CABG for unstable angina, between February 2009 and March 2010, was collected and analysed. Results: Total 35 patients of unstable angina had undergone CABG (M=29, F=6). Mean age was 58.25±9.62. Sixty five percent of the patients were from New York Heart Association (NYHA) class-IV. Regarding pre-operative risk factors, 35% had diabetes mellitus (DM), 22% had previous Myocardial infarction (MI), 3% had pulmonary Hypertension, 3% had uncontrolled hyperlipidemia, 40% had positive history of smoking, 17% had positive family history of IHD and 82% had triple vessel disease. None of the patients died. Mild ionotropic support was required in 48% of the patients. Two patients had acute confusional state; none of the patients had stroke or renal failure requiring dialysis. However 4 patients had disturbed renal profile. Pulmonary complications occurred in one patient. Conclusion: Coronary artery bypass surgery in patients with unstable angina has comparable morbidity and mortality in our setup and should be performed where indicated Keywords: Unstable angina, CABG, IHD, outcome